Physical activity-based nutrition educational games interventions for elementary school children - Khasana, Tri Mei; Ngaisyah, Rr Dewi (Universitas Gadjah Mada, 2022)
Purpose: An approach that can be used in delivering messages to children is the gamification method or game-based learning. This study aims to determine the effect of physical activity-based nutrition educational games on school children's nutritional status and nutrition knowledge. Methods: This study used a quasi-experimental method with a one-group pretest-posttest with a control design. The intervention group was given physical activity-based nutrition educational games, namely